CLINICAL FEATURES OF EMPATHY AND EMOTIONAL REGULATION DISORDERS IN DISSOCIATIVE PERSONALITY DISORDER (IN THE CONTEXT OF THE UZBEK CULTURE) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This scientific article analyzes the clinical features of empathy and emotional regulation disorders within the framework of dissociative personality disorder (DSB) in the Uzbek cultural context. Cultural collectivism, family hierarchy, social control, and gender stereotypes significantly influence the manifestation of dissocial traits. The article covers diagnostic complexities, issues of differential diagnosis, and culturally sensitive therapeutic approaches. An emerging body of research has begun to elucidate disturbances to social cognition in specific personality disorders (PDs). No research has been conducted on patients with Mixed Personality Disorder (MPD), however, who meet multiple diagnostic criteria. Further, very few studies have compared social cognition between patients with PD and those presenting with symptomatic diagnoses that co-occur with personality pathologies, such as anxiety disorder (AD). The aim of this study was to provide a detailed characterization of deficits to various aspects of social cognition in MPD and dissociate impairments specific to MPD from those exhibited by patients with AD who differ in the severity of personality pathology.